Biomass Equations for Tropical Forest Tree Species in Mozambique - Rosta Mate (Forests, 2014)
Chanfuta (Afzelia quanzensis Welw.), Jambire (Millettia stuhlmannii Taub.) and Umbila (Pterocarpus angolensis D.C.) are, among others, three of the main tropical tree species producing commercial timber in Mozambique. The present study employed destructive biomass estimation methods at three localities in Mozambique (Inhaminga, Mavume, and Tome) to acquire data on the mean diameter at breast height (DBH), and height of trees sampled in 21 stands each of Chanfuta and Jambire, and 15 stands of Umbila. Mean diameter at breast height (DBH) (ob) for Chanfuta, Jambire, and Umbila was: 33.8 ± 12.6 (range 13.5–61.1), 33.4 ± 7.4 (range 21.0–52.2), and 27.0 ± 9.5 (range 14.0–46.5) cm. The mean total values for biomass (kg) of trees of Chanfuta, Jambire, and Umbila trees were 864, 1016, and 321 respectively. The mean percentages of total tree biomass as stem, branch and leaf respectively were 54, 43, and 3 for Chanfuta; 77, 22, and 1 for Jambire; and 46, 51, and 3 for Umbila. The best fit species-specific equation for estimating total above ground biomass (AGB) was the power equation with only DBH considered as independent variable yielding coefficient of determination (R2) ranging from 0.89 to 0.97. At stand level, a total mean of 27.3 tons ha−1 biomass was determined of which studied species represented 94.6%. At plot level, total mean biomass for Jambire was 11.8 tons ha−1, Chanfuta and Umbila 9.9 and 4.1 tons ha−1 respectively. The developed power equation fitted total and stem biomass data well and could be used for biomass prediction of the studied species in Mozambique.